Program Edukasi Prevensi Longsor Lereng sebagai Aplikasi Teknologi Bioengineering: Slope Landslide Prevention Education Program as an Application of Bioengineering Technology - Souisa, Matheus; Nanlohy, Pieldrie; Sapulete, Sisca Madonna; Elake, Alexander Yosep; Manuhutu, Fredrik; Lebang, Annamaintin Kobong; Ely, Sufilman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Climate change has triggered increased rainfall intensity and exacerbated the risk of disasters, especially landslides in the tropical hilly areas of Ambon Island. This community service activity was carried out in Karang Panjang Village, Sirimau District, Ambon City, to increase public awareness and knowledge about the impacts of climate change and preventive strategies for slope landslides. Activities include geoscience and bioengineering-based education and direct practice of planting vetiver grass (Chrysopogon zizanioides) as a natural solution for slope prevention. The evaluation results showed an increase in public understanding by 24.7% after participating in a series of socialization activities. In addition to gaining knowledge about the causes and dynamics of slope stability, residents were also equipped with skills to plant and maintain vetiver independently and sustainably. This program proves that an educational and participatory approach can be a strong foundation for community-based disaster mitigation.